Systematic Review of Environmental Uncertainty, Environmental Management Accounting and Sustainable Performance - Alwan, Abdulwahab Razzaq; Maelah, Ruhanita (Journal of Ecohumanism, 2024)
Sustainable performance has emerged as a critical concern in the modern era. Consequently, numerous scholars and researchers are exploring innovative approaches across various disciplines within the social and applied sciences. While the advantages of environmental management accounting (EMA) are well-documented, environmental uncertainty is insufficiently studied yet in many countries and industries. This systematic review seeks to identify the barriers, including environmental uncertainty, that hinder the implementation of EMA practices. Additionally, it examines the scholarly flow and publication toward literature enrichment and practical implementations. The study complies with the Preferred Reporting Items for Systematic Reviews (PRISMA) guidelines. conducted on fifty-one primary articles from Web of Science, Science Direct, and ProQuest databases published in the period 2000-2024. The findings reveal several compelling reasons for adopting EMA to improve sustainable performance, despite challenges like environmental uncertainty that obstruct the implementation of effective EMA practices toward performance sustainability.